Pollen and biomarker record of Lake Dojran - Alessia Masi; Alexander Francke; Caterina Pepe; Matthias Thienemann; Bernd Wagner; Laura Sadori (PANGAEA, 2017)
A sediment sequence (Co1260, 717 cm) from Late Glacial to Holocene of Lake Dojran, located at the border between Greece and F.Y.R. of Macedonia, has been investigated to provide a high-resolution pollen and NPPs analysis. Percentage, concentration and influx values have been interpreted to reconstruct the vegetational dynamics of the last 12500 years. Late Glacial is characterized by steppic taxa replaced by Holocene vegetation after 11500 yr BP. Mesophilous plants dominate for the entire Holocene. The first human trace is clear since 5000 yr BP, but the start of a strong human impact is dated at 2600 yr BP. The data have been also compared with other proxies available for the same core to better comprehend the past climatic dynamics. Geochemical data are available at doi:10.1594/PANGAEA.860791. Biomarkers used in the comparison with pollen have been included in the present repository.
Supplement to: Masi, A et al. (2018): Vegetation history and paleoclimate at Lake Dojran (FYROM/Greece) during the Late Glacial and Holocene. Climate of the Past, 14(3), 351-367, https://doi.org/10.5194/cp-14-351-2018